Crime and local television news : dramatic, breaking, and live from the scene - Lipschultz, Jeremy Harris, 1958- (LEA's communication series., 2002)
This volume offers an analysis of crime coverage on local television, exploring the nature of local television news and the ongoing appeal of crime stories.